2018
DOI: 10.1371/journal.pone.0190406
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol toxicity differs depending on the time of day

Abstract: Ethanol is one of the most commonly abused drugs and consequently its toxic and psychoactive effect has been widely investigated, although little is known about the time-dependent effects of this drug. In the present research zebrafish was used to assess daily rhythms in ethanol toxicity and behavioural effects, as well as the temporal pattern of expression of key genes involved in ethanol detoxification in the liver (adh8a, adh5, aldh2.1 and aldh2.2). Our results showed marked differences in the mortality rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…Mice with binge alcohol drinking at ZT12 had higher serum alcohol levels than ZT0, and serum LPS levels were highest when gavage was performed at ZT4 or ZT8 . Exposure of zebrafish larvae to 5% ethanol for 1 hour can be fatal, and a previous study found that mortality was highest with exposure at ZT2 and lowest at ZT18, indicating the time‐dependent effects of alcohol . Mice with albumin promoter‐driven Cre recombinase ( Alb ‐Cre mice) have Cre expression selectively in hepatocytes and hepatic stellate cells (HSCs) .…”
Section: Functional Roles and Therapeutic Potentials Of Melatonin Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice with binge alcohol drinking at ZT12 had higher serum alcohol levels than ZT0, and serum LPS levels were highest when gavage was performed at ZT4 or ZT8 . Exposure of zebrafish larvae to 5% ethanol for 1 hour can be fatal, and a previous study found that mortality was highest with exposure at ZT2 and lowest at ZT18, indicating the time‐dependent effects of alcohol . Mice with albumin promoter‐driven Cre recombinase ( Alb ‐Cre mice) have Cre expression selectively in hepatocytes and hepatic stellate cells (HSCs) .…”
Section: Functional Roles and Therapeutic Potentials Of Melatonin Andmentioning
confidence: 99%
“…22 Exposure of zebrafish larvae to 5% ethanol for 1 hour can be fatal, and a previous study found that mortality was highest with exposure at ZT2 and lowest at ZT18, indicating the time-dependent effects of alcohol. 23 Mice with albumin promoter-driven Cre recombinase (Alb-Cre mice) have Cre expression selectively in hepatocytes and hepatic stellate cells (HSCs). 24 Zhang et al generated Alb-Cre-mediated liver-specific BMAL1 knockout mice and found that these mice had higher serum aminotransferase (ALT) levels and liver steatosis compared to control mice after chronic and binge alcohol feeding.…”
Section: Alcoholic Liver Diseasementioning
confidence: 99%
“…Moreover, some chemotherapeutic agents increase their efficacy and reduce their toxicity in cancer patients when administered, taking into account the endogenous clock time [ 2 , 25 , 26 ]. In addition, alcohol toxicity differs according to the time of intake and increases when alcohol is consumed in the morning compared to evening intake [ 27 ].…”
Section: Elementary Glossary Of Chronobiologymentioning
confidence: 99%
“…In this context, emerging evidence indicates that correct chronotherapy by synchronizing drug delivery with the endogenous physiological rhythm may be used to optimize treatment efficacy. In fact, adjusting the administration of some drugs to the time has been shown to improve their therapeutic effects and reduce off-target side effects [ 2 , 25 , 26 , 27 ]. It is more difficult to therapeutically restore a normal rhythmicity once it is disrupted.…”
Section: Interrelationship Between Disorders Of Chrono-organization and Thyroid Diseasesmentioning
confidence: 99%
“…In this context, recent research has revealed a daily rhythm in the effects of ethanol in zebrafish, characterized by higher mortality rates in larvae exposed to 5% ethanol at the beginning of the day (80%) than in the middle of the night (6%). In addition, behavioral effects in adults exposed to 1% ethanol were also more severe during the day, with key genes involved in ethanol detoxification in the liver showing circadian rhythmicity in continuous darkness (DD) (183).…”
Section: Time-dependent Stress Responses and Detoxification Rhythmsmentioning
confidence: 99%